1 Crore+ students have signed up on EduRev. Have you? 
f (x*y) = f(x) + f(y)
f(2401) = 10/3 and f(729) = 18
then f(343 * √3) = ?
Given, f(2401) = 10/3
⇒ f(49*49) = 10/3
⇒ f(49) + f(49) = 10/3
⇒ 2 * f(49) = 10/3
⇒ 2 * f(7*7) = 10/3
⇒ 2 * [f(7) + f(7)] = 10/3
⇒ 4 * f(7) = 10/3
⇒ f(7) = 5/6
Also given that, f(729) = 18
⇒ f(3^{6}) = 18
⇒ f((√3)^{12}) = 18
f(√3)^{12}) can be rewritten as: f [(√3)^{6} * (√3)^{6})] = f [(√3)^{6}]+ f [(√3)^{6}]
f [(√3)^{6})] can be rewritten as: f [(√3)^{3} * (√3)^{3}] = f [(√3)^{3})] + f [(√3)^{3}]
f((√3)^{3}) can be rewritten as: f [(√3)^{2} * √3)] = f((√3)^{2}) + f((√3))
f(√3)^{2 }can be rewritten as: f(√3 * √3) = f(√3) + f(√3)
So, f(√3)^{12}) can also be expressed as:
f(√3) + f(√3) + f(√3) + f(√3) + ... upto 12 terms = 12 * f(√3)
So, 12 * f(√3) = 18
⇒ f(√3) = 3/2
So, f(343 * √3) = f(343) + f(√3)
= f(7^{3}) + f(√3)
= 3*f(7) + f(√3)
= 3 * 5/6 + 3/2
= 4
This is very simple :
f(x) = 2x+2
f(3) = 2*3+2=8
f(f(3))= 2*f(3)+2
= 2*8+2
= 18
Hence (A) is the answer
A certain function f satisfies the equation f(x)+2*f(6x) = x for all real numbers x. The value of f(1) is
Here's the Solution :
f(1)+2*f(61)=1......... (1)
f(5)+2*f(65)=5......... (2)
Substituting we have (2) in (1) we have :
3f(1)=9,
Hence answer f(1)=3.
Hence (A) is the correct answer.
If f(x) = x^{3}  4x + p, and f(0) and f(1) are of opposite sign, then which of the following is necessarily true ?
We have
=> f(0) = 0^{3}– 4(0) + p = p.
=> f(1) = 1^{3}  4(1) + p = p – 3.
If P and P – 3 are of opposite signs then p(p – 3) < 0.
Hence 0 < p < 3.
Let f(x) be a function satisfying f(x) f(y) = f (xy) for all real x, y. If f (2) = 4, then what is the value of f (1/2)?
We need to find f(1/2).
According to the question, f(x) * f(y) = f(xy).
So, f(2) * f(1/2) = f(2*1/2) = f(1). (i)
But we do not know f(1).
Using the same formula, f(1)*f(2) = f(1*2) ;
i.e. f(1)*f(2) = f(2) f(1) = 1.
Substituting for f(1) in (i), we get f(2) * f(1/2) = 1.
f(2) = 4, so f(1/2) = 1/4.
For two positive integers a and b define the function h(a,b) as the greatest common factor (G.C.F) of a, b. Let A be a set of n positive integers. G(A), the G.C.F of the elements of set A is computed by repeatedly using the function h. The minimum number of times h is required to be used to compute G is
Let A = { a_{1}, a_{2}, a_{3}, a_{4}, ................, a_{n }}
Initially, the function 'h' is applied to a1 and a2 and obtain a G.C.F.
Now, the function 'h' is applied to the HCF of a_{1} and a_{2} and the next number a_{3}. This process is continued till the last number.
The final G.C.F is the G.C.F of the set A and the number of times we used the function 'h' is 1 [for a1 & a2 ] + (n2) [for the rest of the values] i.e n1.
Let f (x) = max (2x + 1, 3 − 4x), where x is any real number. Then the minimum possible value of f(x) is :
f(x) is the maximum value of 2x + 1 and 3 – 4x.
Here, we see that in 1 place, x is added to something else, while in the other equation (3 – 4x), x is subtracted from something else.
So, in the 1st equation, as x goes higher, f(x) will become bigger, while in the second case, when x goes bigger, the value of f(x) goes smaller, and it will be viceversa when x goes lower.
So, we need to find an optimum solution, which we can obtain by equating both the equations.
2x + 1 = 3 – 4x. On solving, we get x = 1/3 and f(x) = 5/3.
If we put any value more than 1/3, 2x + 1 becomes high, and f(x) increases.
If we put any value less than 1/3, 3 – 4x becomes high, and f(x) increases.
So, for x = 1/3, f(x) = 5/3 is the minimum possible value.
A quadratic function f(x) attains a maximum of 3 at x = 1. The value of the function at x = 0 is 1. What is the value of f(x) at x = 10 ?
Let, the quadratic equation be ax^{2} + bx + c. So, f(x) = ax^{2} + bx + c
At x = 0, the value of function is 1.
x = 0, f(x) = 1
ax^{2} + bx + c = a * 0 + b * 0 + c = c
c = 1.
At x = 1, f(x) = 3
x = 1, f(x) = 3
a *1 + b * 1 + c = 3
Since c = 1, a + b = 2.
Also, we know that f(x) is maximum when x = 1. If f(x) is maximum, (dx/dt)(f(x)) = 0
Differentiating f(x), we have d/dt (ax^{2} + bx + c) = 2ax + b
At x = 1, 2ax + b = 0.
2a + b = 0.
b = 2a.
Substituting we have a + b = 2, or a + 2a = 2. a = 2. So, b = 4.
So the equation is 2x^{2} + 4x + 1.
At x = 10, the value is 2 * 100 + 4 * 10 + 1 i.e 159.
A function f(x) satisfies f(1) = 3600, and f(1) + f(2) +...+ f(n) = n² f(n), for all positive integers n > 1. What is the value of f(9) ?
f(1) = 3600 , f(1) + f(2) = 4 * f(2).
f(2) = f(1)/3. We can write this as f(2) = f(1) * 1/3.
Now, f(1) + f(2) + f(3) = 9 * f(3).
f(3) = f(1) + f(2) / 8. We know f(2) = f(1) / 3.
So, f(3) = f(1) + (f(1)/3) / 8.
We can write this as f(3) = f(1) *1/3 * 2/4. Since we already have f(1) * 1/3, we write it in such a way that the equation has f(1) * 1/3 and then what comes rest, so that we can generalize
Calculating similarly for f(4), we get f(4) = f(1) * 1/3 * 2/4 * 3/5.
So, f(9) will be f(1) * 1/3 * 2/4 * 3/5 * 4/6 * 5/7 *6/8 * 7/9 * 8/10.
=> f(9) = (f(1) * 1 * 2) / (9 *10).
=> f(9) = 3600 * 2/ 9 * 10 = 80.
Let g (x) be a function such that g (x + 1) + g (x – l) = g (x) for every real x. Then for what value of p is the relation g (x + p) = g (x) necessarily true for every real x ?
Given, g (x+1) = g (x) – g (x1)
Let g (x) = p and g (x1) = q.
Then, g (x+1) = g (x) – g (x1) = p – q
g (x+2) = g (x+1) – g (x) = p – q – p = q
g (x+3) = g (x+2) – g (x+1) = qp + q = p
g (x+4) = g (x+3) – g (x+2) = q  p
g (x+5) = g (x+4) – g (x+3) = q –p +p = q = g (x1)
So, we see g (x+5) = g (x1).
Thus, entry repeats after 6 times i.e p = 6.
72 videos64 docs92 tests

Use Code STAYHOME200 and get INR 200 additional OFF

Use Coupon Code 
72 videos64 docs92 tests








